Therapeutic Reference Range for Clozapine Plasma Levels in Parkinson’s Disease or Dementia: A Systematic Review and Individual Participant Data Meta-analysis - Kuzo, Nazar; Piras, Marianna; Lutz, Ulrich C.; Haen, Ekkehard; Eap, Chin B.; Hiemke, Christoph; Paulzen, Michael; Schoretsanitis, Georgios (Pharmacopsychiatry, 2025)
Clozapine is a recommended treatment for psychotic symptoms in patients with Parkinson’s disease (PD) and/or dementia. However, the therapeutic reference range for clozapine in these patients has not been established hitherto.The study was performed in three university hospitals in Germany and Switzerland, including clozapine-treated patients with PD and/or dementia. The primary outcome was tolerability based on reports of adverse drug reactions and/or changes in laboratory tests or electrocardiogram and/or clozapine discontinuation. We meta-analyzed demographic and pharmacokinetic parameters in patients tolerating clozapine well versus not. A meta-analytic summary receiver operating characteristic (SROC) to establish the clozapine upper level associated with poor tolerability was estimated.We analyzed a total of 99 patients suffering from PD (56.6%) and/or dementia (49.5%) with a mean age of 70.3±9.5 years and 41.4% females; poor tolerability was reported in 26 of 99 patients (26.3%). When comparing patients with and without poor tolerability, there were no differences in age, body mass index, sex, smoking, or clozapine dose, nor did we find statistically significant differences in clozapine levels (standardized mean difference 0.46, 95% confidence interval − 0.04 to 0.96, p=0.07), and heterogeneity was low (I2=0.0%). Clozapine blood levels above 193 ng/mL were associated with poor tolerability (SROC area-under-curve 0.6, sensitivity 39.7%, specificity 79.9%).One of four patients with PD and/or dementia treated with clozapine did not tolerate clozapine well, which was associated with a trend toward elevated clozapine concentrations. Monitoring drug levels may help to improve tolerability in these patients.
Keywords: therapeutic drug monitoring; clozapine; Parkinson’s disease; dementia